A simple method to detect leaks after left atrial appendage occlusion with Watchman. (10th July 2020) - Ayhan, Hüseyin; Mohanty, Sanghamitra; Gedikli, Ömer; Trivedi, Chintan; Canpolat, Ugur; Tapia, Alfredo Chauca; Chen, Qiong; Della Rocca, Domenico G.; Gianni, Carola; Salwan, Anu; Annanab, Alisara; MacDonald, Bryan; et al.
Abstract: Background: We evaluated the efficacy of a new method in identifying peri‐device leak (PDL) using morphology of the thrombus formed inside the left atrial appendage (LAA) as seen on follow‐up transesophageal echo (TEE). Method: A total of 291 consecutive patients undergoing Watchman procedure were included in this analysis. TEE was performed at 45 days postprocedure. Based on the presence of the thrombus inside the LAA behind the device, patients were grouped as (1) white (W) group: LAA completely filled with thrombus ( n = 101), 2) nonwhite (NW) group: LAA completely black or mixed (part black and part white; n = 190). Follow‐up TEE was repeated at 6 and 12 months. Results: Baseline characteristics were comparable between groups except the device size, number of patients with chicken‐wing morphology, and prevalence of left atrial "smoke" that were significantly higher in the NW group. Detection of black appearance was comparable between the pre‐coil closure image and the NW population (26/36 [72.2%] vs 99/154 [64.3%], p = .37). After adjusting for clinically relevant covariates, NW appearance of the LAA was associated with the presence of significant leak (odds ratio: 47.96, 95% confidence interval: 2.91–790.2, p < .001). The 11 patients with mixed appearance at the 6‐month TEE remained unchanged (part black and part white) at the 12‐month TEE. LAA appearance was white in all 36 patients following coil closure. Conclusion: Our findings demonstrated white and nonwhite appearance of the appendage on TEE to be reliable markers of complete closure and leak respectively, following LAA occlusion with the Watchman device.